Investment and land disputes in Tanzania: A vehicle for investment legal reform - lendita, Simon W (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the award of Master’s Degree of Laws in Commercial law (LL.M. CL) of Mzumbe University